Permeation kinetics of nano-emulsified tarragon essential oil in fermented pickled cucumbers by FTIR, antioxidant capacity potentiometry, and antimicrobial properties - Mahdi Nikkhah; Abdollah Hematian Sourki; Askar Ghani (Food Production, Processing and Nutrition)
Abstract The permeation kinetics of nano-emulsified tarragon essential oil (TEO) into fermented pickled cucumber texture was measured by Fourier transform infrared spectrometry (FT-IR) and antioxidant capacity potentiometry. The objective was to evaluate how nano-emulsion affect the sensory, antioxidant, physicochemical, and microbial flora characteristics of the pickled cucumbers. Oil-in-water nano-emulsions (100, 200, 400 and 800 mg L−1) were prepared by ultrasonic waves and were added to the brine/vinegar and cucumber mixture. The analysis of chemical compounds by gas chromatography showed that the main components of TEO were methyl chavicol, Z-β-ocimene, E-β-ocimene, limonene, and methyl eugenol. The average particle size of nano-emulsions was ranging from 19.03 to 218.6 nm. The sensory evaluation of pickled cucumber containing nano-emulsified TEO showed that higher TEO concentrations increased the sensory characteristics significantly in the pickled cucumbers, such as their color, aroma, taste, mouthfeel, texture crispness, and overall acceptance. The microbial test proved the inhibitory effect of TEO on Penicillium expansum and Aspergillus flavus species. According to the results of FTIR, the nano-emulsified TEO penetrated well into the pickled cucumber texture. The antioxidant capacity of the pickled cucumbers revealed that by increasing the concentration of TEO, the antioxidant capacity of the pickled cucumber texture increased significantly (p < 0.05). Using nano-emulsified TEO can be a good replacement for dried vegetables in producing fermented pickled cucumbers. Graphical Abstract